1996
DOI: 10.1073/pnas.93.24.14059
|View full text |Cite
|
Sign up to set email alerts
|

The AML1/ETO fusion protein activates transcription of BCL-2

Abstract: The AML1 gene, located on chromosome 21, is involved in several distinct chromosomal translocations in human leukemia. In t(8;21) acute myelogenous leukemia (AML), the AML1 gene is juxtaposed to the ETO gene located on chromosome 8, generating an AML1͞ETO fusion protein. Both AML1͞ETO and the AML1 proteins recognize the same consensus DNA-binding motif (TGT͞CGGT), which is found in the promoters of several genes involved in hematopoiesis. We found that two myeloid leukemia cell lines with the t(8;21) transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 32 publications
(21 reference statements)
5
136
0
1
Order By: Relevance
“…Consistent with this model, when Kasumi AML cells, which harbor t(8;21), were treated with an AML1-ETO antisense oligonucleotide they di erentiated and their proliferation rate slowed (Sakakura et al, 1994). The possibility that CBF oncoproteins also contribute to tumor progression or phenotype by activating a subset of gene regulated by CBFs was recently raised by the observation that AML1-ETO can activate the BCL-2 gene promoter (Klampfer et al, 1996). Again, such gene activation might be potentiated by initial genetic hits which enable higher level expression of AML1-ETO and other CBF oncoproteins.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Consistent with this model, when Kasumi AML cells, which harbor t(8;21), were treated with an AML1-ETO antisense oligonucleotide they di erentiated and their proliferation rate slowed (Sakakura et al, 1994). The possibility that CBF oncoproteins also contribute to tumor progression or phenotype by activating a subset of gene regulated by CBFs was recently raised by the observation that AML1-ETO can activate the BCL-2 gene promoter (Klampfer et al, 1996). Again, such gene activation might be potentiated by initial genetic hits which enable higher level expression of AML1-ETO and other CBF oncoproteins.…”
Section: Discussionmentioning
confidence: 80%
“…Blockade of di erentiation is not absolute, as the majority of leukemic blasts harboring these oncoproteins express di erentiation markers such as MPO. The possibility that CBF oncoproteins activate genes leading to tumor progression, such as the BCL-2 gene (Klampfer et al, 1996), or partial di erentiation must also be considered 1993). For oligonucleotide competition, unlabeled competitors were added 5 min prior to the radiolabeled probe.…”
Section: Nuclear Extraction and Gel Shift Analysismentioning
confidence: 99%
“…Consistent with a negative e ect on AML1 function, AML1/ETO has been shown to block both the di erentiation of myeloid progenitor cell lines and the ability of AML1 to activate myeloid speci®c promoters (Kitabayashi et al, 1998;Westendorf et al, 1998). In contrast to its role as a dominant inhibitor, AML1/ETO can activate the BCL-2 promoter in U937 cells, an e ect not seen when AML1 or ETO are overexpressed in these cells (Klampfer et al, 1996). AML1/ETO expression in a knock-in model, and in retrovirally transduced murine bone marrow stem cells, caused increased progenitor cell self-renewal capacity and dysplastic hematopoiesis (Okuda et al, 1998).…”
Section: Introductionmentioning
confidence: 82%
“…The arrows in a and b indicate the location of the speci®c PCR products for IL-3, and GAPDH, respectively CSFR promoter) and AML1/EV1-can activate AP-1 activity (Mitani et al, 1994). The transcriptional activities of AML1/ETO require the Rhd of AML1, and varying amino acids contributed by ETO (Klampfer et al, 1996;Lenny et al, 1995;Rhoades et al, 1996) whereas the activation of AP-1 activity by AML1/EVI-1 requires EVI-1 amino acids and not the Rhd (Mitani et al, 1994). We, and others, have now demonstrated that AML1/ETO and TEL-AML1 act as repressors of basal transcription of the IL-3 promoter and TCR-b enhancer in T cell lines (Uchida et al, 1997), or in C33a cervical carcinoma cells Meyers et al, 1995), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…TCRb, GM-CSF, IL-3) (Frank et al, 1995;Meyers et al, 1995;Uchida et al, 1997) and activate the promoter of other genes (e.g. BCL-2, M-CSFR) (Klampfer et al, 1996;Rhoades et al, 1996). Similarly, the TEL-AML1 fusion protein has been shown to repress T-cell receptor b enhancer activity , but have no e ect by itself on M-CSF receptor promoter activity (Fears et al, 1997).…”
Section: Introductionmentioning
confidence: 99%